Marxism and Medieval Studies
1 online resource (406 pages)
Keywords: This volume is a unique publication as it examines the Marxist attitudes in East Central European historiography and archaeology for the first time, with an emphasis on the co-existence of Marxist and other methodologies between the 1950s and 1970s in the local historiographies in question. Its approach is to distinguish between pseudo-Marxism as an ideological tool on the one hand, and Marxism in the form of historical materialism as a way to interpret the medieval world on the other. Contributors are: Florin Curta, Piotr Guzowski, Adam Hudek, Tereza Johanidesová, Jitka Komendová, Jiří Macháček, Andrzej Marzec, Martin Nodl, Attila Pók, David Radek, Tadeusz Paweł Rutkowski, Iurie Stamati, Rafał Stobiecki, Gábor Thoroczkay, Przemysław Wiszewski, Piotr Węcowski, Martin Wihoda, and Dušan Zupka.